The Effect of Single-Parent Parenting Style on the Socio-Emotional Development of Children Aged 5-6 Years - Habibi, MA Muazar (Universitas Lancang Kuning, 2023)
This research aims to provide an overview of the impact of single-parenting styles on the social-emotional development of children aged 5-6 years. The focus of this study is to delve into the concept of parenting styles and the factors influencing them in the interaction between parents and children. This research is important given the increasing number of single parents in Indonesia, making it crucial to understand its impact on the social-emotional development of children. The research was conducted in Mataram City, West Nusa Tenggara, using a qualitative descriptive method in the form of a case study. The research subjects consisted of 2 boys and 2 girls aged 5-6 years. Data were collected through observation, interviews, and documentation. The research results indicate that children experienced difficulties in solving problems in the games they played, as well as in understanding their rights and responsibilities when their developmental indicators were still in the early stages. As the indicators developed, children began to avoid games they considered unsuitable for them (MB). They also started eating and drinking alone when they reached the expected stage of development (BSH), and it was found that they played alone without parental supervision due to the lack of attention given by parents when the developmental indicators were highly advanced (BSB).